A simple method for phase control in two-dimensional perovskite solar cells. Issue 39 (1st October 2018) - Ma, Chunqing; Lo, Ming-Fai; Lee, Chun-Sing
Abstract : Suppressed low-n phases by using DMSO enable high performance GAMA4 Pb4 I13 PSCs. Abstract : Two-dimensional (2D) perovskites with n = 4 have attracted much attention recently and the low-n ( e.g. n = 1) phases in these 2D perovskites have been found to act as carrier traps, leading to decreased performance. In this work, we demonstrate a simple method to suppress the formation of low-n phases by using dimethyl sulfoxide (DMSO) as a co-solvent. The present 2D perovskites with alternating cations in the interlayer space (ACI) exhibit enhanced carrier lifetime and charge transport by suppressing low-n phases. The optimized 2D ACI-based perovskite solar cell shows a PCE of 12.8%, which is also the highest efficiency for ACI-based perovskite solar cells, and is almost 3 times higher than that of the non-DMSO treated devices.